Pengaruh Kualitas Produk, Citra Merek Dan Kepuasan Konsumen Terhadap Keputusan Pembelian Virtako di UD. Rizky Desa Pematang Jering - Nainggolan, Benhart (Management And Business Progress, 2024)
This study aims to determine " The Effect of Product Quality, Brand Image and Consumer Satisfaction on Virtako Purchasing Decisions in UD Rizky Pematang Jering Village. The method of determining the sample used in this study is to use the non probability sampling formula as many as 30 samples who are farmers in Pematang Jering Village. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Product Quality variable (X1) has an effect on the Purchasing Decisions variable (Y). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is accepted, meaning that the Brand Image variable (X2) has an effect on the Purchasing Decisions variable (Y). Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is rejected, meaning that the Consumer Satisfaction variable (X2) has no effect on the Puchasing Decisions variable (Y). Based on the results of the analysis of hypothesis 4, it can be concluded that the forth hypothesis is accepted, meaning that the Product Quality variable (X1), Brand Image variable (X2), and Consumer Satisfaction variable have a joint effect on the Purchasing Decisions variable (Y).